Evaluation of factors associated with the detection of incidental prostate cancer after open prostatectomy for benign prostatic hyperplasia. (29th September 2021) - Kizilkan, Yalcin; Eroglu, Unsal; Senel, Samet; Yildizhan, Mehmet; Balci, Melih; Aykanat, Ibrahim Can; Aktas, Binhan Kagan; Bulut, Suleyman; Guzel, Ozer; Gokkaya, Cevdet Serkan; Aslan, Yilmaz; Ozden, Cuneyt; et al.
Summary: We aimed to evaluate the incidental prostate cancer (PCa) rate and predictive factors in patients who underwent open prostatectomy (OP) with a pre‐diagnosis of benign prostatic hyperplasia (BPH). This study included patients with a pre‐diagnosis of BPH, who underwent OP due to symptomatic prostate enlargement. Our database included age, medications, prostate‐specific antigen (PSA), free/total PSA ratio, PSA density, digital rectal examination (DRE), prostate volume, serum neutrophil/lymphocyte ratio, platelet/lymphocyte ratio, aspartate aminotransferase/alanine aminotransferase ratio, presence of metabolic syndrome (MetS) and histopathological results after OP. Of the 430 patients that underwent OP, 406 (94.4%) with a benign pathological diagnosis were evaluated as the benign group and 24 (5.6%) detected to have PCa constituted the incidental PCa group. The rate of incidental PCa was much higher in the elderly patients. The cut‐off value of age was 71.5 years in the PCa group according to the receiver operating characteristic curve analysis. According to the multivariate analysis, DRE and the presence of MetS were effective in predicting PCa ( p < .001 and p = .031, respectively). DRE was found 16 times more effective and MetS was 2.8 times more effective than the other parameters. Our results showed that DRE and the presence of MetS could be useful predictive factors of incidental PCa in OP.